Brasiliens Süd-Süd-Kooperation mit Afrika. Eine neue atlantische Allianz? - Stolte, Christina (Regionen und Regionalismus in den Internationalen Beziehungen, 2016)
Keywords: Brasilien; Außenpolitik; Afrika; Interregionalismus

Brazil's Africa Strategy. Role Conception and the Drive for International Status - Stolte, Christina (Palgrave Macmillan, 2015)
Keywords: Brazil; Foreign Policy

Insider and Outsider Strategies of Influence: The BRICS’ Dualistic Approach Towards Informal Institutions - Cooper, Andrew F.; Stolte, Christina (New Political Economy, 2019)
The challenge of ‘emerging’ countries in the 21st century has been conducted in a much more peaceful manner than in past eras when power transitions were most commonly accompanied by war. The hallmark of this peaceful transition has been the elevation of the G20, a forum in which established and emerging powers jointly deal with global economic issues and which–despite or precisely because of its informal character–has become the prime forum for global economic governance. Significantly, however, this new openness and flexibility of the international system and its increasing informalism have not only provided an avenue for emerging powers to be integrated into the inner circle of global economic governance, but have also allowed them to set up alternative institutions. By forming their own exclusive BRICS group in parallel to their membership in the G20, emerging powers have pursued a dualistic strategy that allows them to be simultaneously institutional ‘insiders’ and ‘outsiders’. The article focuses on this seemingly ambiguous international behaviour and explains why the BRICS have opted for this dualistic approach. Far from being socialised into the established system, the oppositional psychology of the past has not disappeared completely.
CRIS-Team Scopus Importer:2020-02-21
Keywords: BRICS; Emerging powers; G20; global economic governance; informal institutions